Making breakthrough innovation happen : how eleven Indians pulled off the impossible - Munish, Porus (London, 2013)
India is known as a country not of innovation but of improvisation-or 'Jugaad', as they say in Hindi. But that has begun to change. We have enough examples in this country of people who have turned industry norms upside down to pull off the impossible in their fields. Eleven such case studies are featured in the book, including: Titan, which came out with the slimmest water-resistant watch in the world; Su-Kam, a power backup company that did not fit into an existing industry but ended up creating a new one; Shantha Biotech, which developed a low-cost Hepatitis-B vaccine and ushered in the biotechnology age in India; Trichy Police, which rewrote policing paradigms to nip extremism and crime in the bud, thus transforming the city. Through the breakthroughs achieved by these organizations, Porus Munshi shows that to do what is considered 'impossible' in your particular industry, you have to be subversive and think differently. In the process, if the existing business model needs to be turned on its head, then so be it!
Keywords: "Technological innovations, India"